Ethnobotanical aspects of Cuspon, Peru: A peasant community that uses 57 species of plants in its various needs - Ramírez, Linder (2020)
It is known that the Andean-Amazon communities throughout history have made a correct and effective use of its floristic resources, which by intelligently domesticating them have become true contributions of Peru for humanity. For this reason, this research focused on determining the aspects ethnobotanicals of the species used by the Cuspon Peasant Community. 150 semi-structured interviews were applied, to collect information regarding: taxonomy, common names, habit or bearing, habitat, way of propagation, part used and ethnobotanical use, to later determine the Cultural Index (CI). The Cuspon community uses 57 species of plants distributed in 48 genera and 30 families; the most representative being the Asteraceaes (11), solanaceae (4), Euphorbiaceae (3), Malvaceae (3), Onagraceae (3) and Urticaceae (3); and the most species Important: Solanum tuberosum L. "potato" (IC = 1.33), Zea mays L. "corn" (IC = 1.31), Chenopodium quinoa Willd. "quinoa" (IC = 1.06), Caesalpinia spinosa (Molina) Kuntze "tara" (IC = 0.97), Capsicum pubescens Ruiz & Pav. "rocoto" (IC = 0.95), Juglans neotropica Diels "walnut" (IC = 0.92), Alnus acuminata Kunth "alder" (IC = 0.86), Cestrum auriculatum L'Hér. "holy grass", Minthostachys mollis (Benth.) Griseb. "muña" (IC = 0.85).